Estimating the Transformer Health Index Using Artificial Intelligence Techniques - Al Qudsi, Alhaytham Y. (2016)
A Master of Science thesis in Electrical Engineering by Alhaytham Y. Al Qudsi entitled, "Estimating the Transformer Health Index Using Artificial Intelligence Techniques," submitted in June 2016. Thesis advisor is Dr. Ayman El-Hag. Soft and hard copy available.